2017
DOI: 10.1002/anie.201709419
|View full text |Cite
|
Sign up to set email alerts
|

Side‐Group‐Mediated Mechanical Conductance Switching in Molecular Junctions

Abstract: A key target in molecular electronics has been molecules having switchable electrical properties. Switching between two electrical states has been demonstrated using such stimuli as light, electrochemical voltage, complexation and mechanical modulation. A classic example of the latter is the switching of 4,4'-bipyridine, leading to conductance modulation of around 1 order of magnitude. Here, we describe the use of side-group chemistry to control the properties of a single-molecule electromechanical switch, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 26 publications
4
84
0
Order By: Relevance
“…The absence of high G value for BPY-N and BPY-2N might be caused by the steric hindrance of the nitro groups, which prevent the pyridine ring from directly binding to the Au electrode at an angle in the electrode-molecule interface. A similar phenomenon has been reported recently by Ismael and co-workers, they found that the BPY decorated with bulky alkyl side-groups reduces the molecule-electrode coupling strength in the high-conductance geometry, thus preventing the formation of high conductance geometry [ 38 ].…”
Section: Discussionsupporting
confidence: 80%
“…The absence of high G value for BPY-N and BPY-2N might be caused by the steric hindrance of the nitro groups, which prevent the pyridine ring from directly binding to the Au electrode at an angle in the electrode-molecule interface. A similar phenomenon has been reported recently by Ismael and co-workers, they found that the BPY decorated with bulky alkyl side-groups reduces the molecule-electrode coupling strength in the high-conductance geometry, thus preventing the formation of high conductance geometry [ 38 ].…”
Section: Discussionsupporting
confidence: 80%
“…where s is an energy shift of the orbital due to interactions with the electrodes,a nd G describes the strength of the coupling that causes abroadening of the orbital resonance,as shown in Figure 1a.I tc an be inferred from the above equations that i) the off-resonance transmission coefficient (and therefore the conductance of the molecular junction) is strongly dependent on the strength of the coupling to the electrodes,a nd ii)if G can be modulated reversibly and reproducibly in response to an external stimulus,t hen this would yield af unctional nanoelectronic device.W ef ocussed our efforts on the use of mechanical forces as the triggering stimuli, because these have been used to exert some degree of control on G by exploiting weak interactions between the metallic electrodes and an eighbouring p-system in a hapto coordination, for instance by using 4-pyridyl contact groups [18] or vicinal phenyl rings. [19][20][21] In the following,wedemonstrate that hemilabile ligands also satisfy the above requirements, with further advantages over the existing strategies lying in chemical control on G modulation, chemically-defined contact configurations,and improved sensitivity and amplitude of conductance changes.T he reason lies in an enhanced metalmolecule coupling in the bidentate contact compared with the monodentate configuration ( Figure 1c), with af ully reversible mono-to-bidentate transition and reproducible behaviour imparted by the hemilabile ligands.…”
Section: Introductionmentioning
confidence: 89%
“…It can be inferred from the above equations that i) the off‐resonance transmission coefficient (and therefore the conductance of the molecular junction) is strongly dependent on the strength of the coupling to the electrodes, and ii) if Γ can be modulated reversibly and reproducibly in response to an external stimulus, then this would yield a functional nanoelectronic device. We focussed our efforts on the use of mechanical forces as the triggering stimuli, because these have been used to exert some degree of control on Γ by exploiting weak interactions between the metallic electrodes and a neighbouring π‐system in a hapto coordination, for instance by using 4‐pyridyl contact groups or vicinal phenyl rings . In the following, we demonstrate that hemilabile ligands also satisfy the above requirements, with further advantages over the existing strategies lying in chemical control on Γ modulation, chemically‐defined contact configurations, and improved sensitivity and amplitude of conductance changes.…”
Section: Introductionmentioning
confidence: 94%
“…1a. Firstly and most importantly, molecular engineering plays a key role in the device functionalization [12,13] because specially designed molecules are able to endow the intrinsic molecular properties, which are directly correlated to their electronic structures, into molecular electronic devices. Secondly and complementarily, interfacial engineering plays an important role in the electrical characteristics of molecular devices [14].…”
Section: Functional Molecular Electronic Devices Through Environmentamentioning
confidence: 99%